2015
DOI: 10.1371/journal.pone.0123290
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Clinically Assessed Hearing Loss; A Cross-Sectional Register-Based Study on a Swedish Population Aged 18 through 50 Years

Abstract: ObjectivesQuestionnaire studies suggest that hearing is declining among young adults. However, few studies have examined the reliability of hearing questionnaires among young adult subjects. This study examined the associations between pure tone audiometrically assessed (PTA) hearing loss and questionnaire responses in young to middle aged adults.Materials and MethodsA cross-sectional study using questionnaire and screening PTA (500 through 6000 Hz) data from 15322 Swedish subjects (62% women) aged 18 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(50 reference statements)
0
7
0
1
Order By: Relevance
“…The influence of communication biases cannot be ruled out, since only very few studies have used objective measures of hearing impairment that bypass these biases, such as tone audiometry. Self-reported hearing impairment appears to be a fairly valid method to estimate its presence in comparison to tone audiometry (Sindhusake et al, 2001;Videhult Pierre et al, 2015;Kamil et al, 2015), but can be prone to information bias. This is illustrated by the within-study discrepancies between different types of measurements of hearing on the total psychosis risk, as previously described in paragraph 2.2.1.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of communication biases cannot be ruled out, since only very few studies have used objective measures of hearing impairment that bypass these biases, such as tone audiometry. Self-reported hearing impairment appears to be a fairly valid method to estimate its presence in comparison to tone audiometry (Sindhusake et al, 2001;Videhult Pierre et al, 2015;Kamil et al, 2015), but can be prone to information bias. This is illustrated by the within-study discrepancies between different types of measurements of hearing on the total psychosis risk, as previously described in paragraph 2.2.1.…”
Section: Discussionmentioning
confidence: 99%
“…Further, all participants were screened to exclude hearing impairment using a validated population questionnaire. 53 For all participants, diagnostic assessment and clinical symptom rating were undertaken by an experienced clinician using the Structured Clinical Interview for DSM-5 (SCID-5) and the 24-item Brief Psychiatric Rating Scale (BPRS). In addition to meeting diagnostic criteria for schizophrenia, patients were further selected on the basis of the characteristics of their hallucinations as assessed by the lifetime psychosis module of the SCID-5, the BPRS item score “hallucinatory behavior” and medical records review.…”
Section: Methodsmentioning
confidence: 99%
“…Subjective hearing studies can be affected by many factors, including sensory cell function [9], general health [10], symptom severity [11], culture [12], expectations [4], and labor market participation [11] and can be di cult to interpret. A cross-sectional study of young and middle-aged people in Sweden reported that the overall prevalence of PTA hearing loss was lower than that of subjective hearing impairment [13]. In addition, it was noted that self-reported hearing di culties underestimated the number of people with hearing loss in those 70 years or older, those with a low poverty index ratio, and those with low education levels [14].…”
Section: Discussionmentioning
confidence: 99%